E-Learning and Student’s Achievement: Fulfilling the Needs for Technology Integration - Shynta Amalia; Muhammad Iqbal Ramdhani (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2018)
The gap between students’ learning level and their level of writing prompted this classroom action research (CAR). E-learning was chosen as a media for students to enhance their understanding in producing a good piece of writing. The results showed that integrating e-learning in writing class contributed to the improvement of students’ writing. E-learning fulfilled the need of extended activities to accelerate students’ comprehension which resulted in their writing achievement. Students who actively participated in e-learning based teaching and learning activities showed a better writing performance in terms of organizing ideas. They also become more active during the classroom discussion due to their awareness of their writing problems.